Peran Kepemimpinan Rendah Hati dalam Memediasi Hubungan Antara Partisipasi Pegawai dan Perubahan Organisasi - Rafidah Elyanis; Riri Lovita; zaitul zaitul (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Organisational change is essential for improving public institutions' efficiency, effectiveness, and competitiveness in delivering services. This study explores the influence of employee participation on organisational change, mediated by humble leadership, within the Dinas Pemberdayaan Masyarakat dan Desa in Padang Pariaman Regency. Using a quantitative research method with total sampling (n = 32), data were collected through a closed-ended Likert-scale questionnaire and analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) via Smartpls 3. The findings reveal that while employee participation does not directly and significantly affect organisational change, it significantly influences humble leadership. In turn, humble leadership significantly impacts organisational change and mediates the relationship between employee participation and organisational change. These results emphasise the critical role of humble leadership in facilitating effective change management by enhancing employee involvement and readiness for transformation in public sector organisations.